The Impact of COVID-19 Pandemic on Medical Imaging Workers: Infection Sources, Awareness and Commitment to relevant Safety Guidelines (Al-Quds Journal for Natural Sciences, 2023)
COVID-19 virus disease is an infectious disease caused by SARS-Cov-2 virus, as the diagnostic imaging department play a  remarkable role in detecting and diagnosing of COVID-19 in early stages, therefore, medical imaging workers should be aware of infection control guidelines to prevent the transmission of the disease. A cross-sectional descriptive study survey  design was conducted from July 15, 2020 to September 15, 2020, in diagnostic imaging departments in Palestine, aimed to evaluate the impact of COVID-19 pandemic on medical imaging workers; in terms of infection sources, awareness and  commitment to relevant safety guidelines. From a 205 valid responses, there was 54.5% governmental, 27.2% private, and 18.3% from NGOs sector. Female were 26.8% and 81.9% holding BA degree, about 41.2% are less than five years of  experience. 36.1% had a previous positive COVID-19 result, of them there was 61.6% due to nosocomial infection. Only 63.2% were confidence of their hospital preparedness for COVID-19, 65.1% felt that their department is capable of dealing  with COVID-19 patients, 43.3% revealed that they had training on handling COVID-19 patients, 58.7% reported that selfreading was their source of information about COVID-19, inadequate training or knowledge about hand hygiene and proper  use of PPE was noted. Our findings emphasize the vital need of expanded COVID-19 pandemic training for medical imaging  workers, as well as related protective measures